Deliverology 101 : a field guide for educational leaders - Barber, Michael, 1955- 4 0 16; 1966- , Moffit, Andy,;Kihn, Paul; 5 Ontario Principals' Council.;U.S. Education Delivery Institute (Thousand Oaks, CA : Corwin Press, 2011)
Provides tips and step-by-step guidance for education leaders on reform delivery, focusing on methods that can yield positive results, and examining reform cases from more than twenty countries.
A joint publication with the U.S. Education Delivery Institute and Ontario Principals' Council.
Includes bibliographical references (p. 272-273) and index.
Professional;Professional.
Keywords: 2 -- 0; 6; School improvement programs.;Educational leadership.;Leadership.; 20; 2